2021
DOI: 10.1007/s10389-021-01609-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of tele visit healthcare services triggered by the COVID-19 emergency: the Trentino Province experience

Abstract: Aim In response to the SARS-CoV-2 emergency, the Competence Centre on digital health ‘TrentinoSalute4.0’ has developed TreC_Televisita, a tele visit solution that meets the needs of the Trentino healthcare system and maintains high-quality patient–doctor interactions while respecting social distancing. This paper highlights how ‘TreC_Televisita’ was integrated into the Trentino healthcare system and its potential to become a structural and durable solution for the future local healthcare service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While these studies have demonstrated the effectiveness and positivity of remote monitoring in cardiology patients, the interpretation of the organisational phenomena that have accompanied these sudden transformations seems much more complex. Organisational resilience in these situations is one of the most difficult challenges in order to make the changes stable over time (Testa et al 2022).…”
Section: Telemonitoring In Cardiologymentioning
confidence: 99%
“…While these studies have demonstrated the effectiveness and positivity of remote monitoring in cardiology patients, the interpretation of the organisational phenomena that have accompanied these sudden transformations seems much more complex. Organisational resilience in these situations is one of the most difficult challenges in order to make the changes stable over time (Testa et al 2022).…”
Section: Telemonitoring In Cardiologymentioning
confidence: 99%
“…The two assessments emphasize the weaknesses of digital health technology in public health. Significant barriers exist to its acceptance, scaling, and integration with healthcare systems and public health programs (Testa et al, 2022). Other factors to consider are the likelihood of measurement bias, particularly for racial and ethnic minority groups-bias caused by unvalidated AI algorithms-and equity concerns when deploying such technology among disproportionately impacted communities.…”
Section: Introductionmentioning
confidence: 99%